Synthesis, crystal structure, Hirshfeld surface analyses and antibacterial activity of 2-fluorobenzylpyridinium tetrabromidocuprate(II) - Chen, Yan-Lin; Li, Xin-Ran; Li, Xiang-Ling; Hu, Bao-Yi; Jiang, Yan; Ni, Chun-Lin (Molecular Crystals and Liquid Crystals, 2025)
In this article, novel organic-inorganic hybrid material, 2-fluorobenzylpyridinium tetrabromidocuprate(II) [2FBzPy] 2 [CuBr 4 ], has been obtained by using a slow evaporation solution-growth method and was characterized by powder X-ray diffraction, infrared spectroscopy, scanning electron microscopy, UV-visible diffuse reflectance spectrum. The compound crystallizes in the monoclinic space group P2 1 /c, and the packing is governed by C − H···Br hydrogen bonding interactions, which was confirmed by the Hirshfeld surface analysis. The results of antimicrobial experiments showed that the compound possessed excellent antimicrobial activity against Staphylococcus aureus and Escherichia coli. RESEARCH HIGHLIGHTS An inorganic-organic hybrid salt [2FBzPy] 2 [CuBr 4 ] was synthesized and characterized. The main intermolecular interaction in [2FBzPy] 2 [CuBr 4 ] crystals have been studied and analyzed. The interactions between different molecules in[2FBzPy] 2 [CuBr 4 ] were examined by Hirshfeld surface analyses. [2FBzPy] 2 [CuBr 4 ] had an optical band gap of 1.69 eV, was a typical semiconductor material with good optical property. The as-synthesized salts exhibits good antibacterial activities against S. aureus and E. coli.